Complication of Nexplanon contraceptive implant requiring intramuscular removal from biceps: A Case Report - Harvey Wang; Yogesh Kolwadkar (Journal of Family Medicine and Primary Care)
Implantable contraceptives provide a temporary, long-acting, and reversible form of contraception. Implant migration is a rare complication, with potential damage to the musculature or neurovascular structures. This is a case of a Nexplanon implant migration into the biceps brachii muscle, requiring surgical removal. Implants that become non-palpable should be immediately visualized with imaging to prevent further nerve or vascular injury and subsequently be removed.